Expatriate Women’s Empowerment and Well-Being: The Mediating Role of Community Embeddedness - Aldabbas, Hazem; Elamin, Abdallah M.; Gernal, Liza; Ahmed, Ahmed Zain Elabdin (Migration Letters, 2023)
Literature has studied the factors affecting people’s well-being, but expatriate women’s empowerment and community embeddedness has been neglected as factors affecting women’s well-being. However, the literature has not examined a relatively new phenomenon: the influence of expatriate women’s empowerment, community embeddedness on women’s well-being. Specifically, this study aims to empirically investigate the relationship between expatriate women’s empowerment and well-being as mediated by community embeddedness. Data were collected in the United Arab Emirates. A total of 161 questionnaires were received among women. The study used multiple regression to examine the study hypotheses. This work finds that there is a direct and significant relationship between women’s empowerment and well-being. Additionally, this study finds that community embeddedness mediates the relationship between women’s empowerment and well-being. Building on empowerment theory, the link between women’s empowerment and well-being is assumed to be explained by community embeddedness. This novel study will contribute to the literature on women’s empowerment and expatriate women’s studies by elucidating the mechanism by which women’s empowerment influences well-being in the United Arab Emirates.